First Record of Creophilus maxillosus (Linnaeus, 1758) (Coleoptera; Staphylinidae) for Yemen: Hairy Rove Beetle of Forensic Entomology - Al-Azab, Abbas Mohammed; Al Raeeini, Wed Abdullah (PSM Biological Research, 2026)
This is the first study of Coleoptera succession on a decomposing rabbit carcass, Oryctolagus cuniculus L., in a shaded area of the laboratory at Thamar University during the winter season 2024 in Dhamar city, Yemen. In the present study, a female specimen of Creophilus maxillosus Linnaeus (Coleoptera, Staphylinidae) was collected from a rabbit carcass as a new record from Yemen. In addition, this record may provide a basis for further faunal surveys and encourage deeper research on the necrophagous insect fauna of Yemen. Thus, the present study emphasizes that a continuous survey of carrion-associated beetles is necessary to improve forensic entomology in the studied region.